2014
DOI: 10.1007/s00709-014-0691-3
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose pretreatment induces salt tolerance in rice (Oryza sativa L.) seedlings: oxidative damage and co-induction of antioxidant defense and glyoxalase systems

Abstract: Salinity in the form of abiotic stress adversely effects plant growth, development, and productivity. Various osmoprotectants are involved in regulating plant responses to salinity; however, the precise role of trehalose (Tre) in this process remains to be further elucidated. The present study investigated the regulatory role of Tre in alleviating salt-induced oxidative stress in hydroponically grown rice seedlings. Salt stress (150 and 250 mM NaCl) for 72 h resulted in toxicity symptoms such as stunted growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 64 publications
5
88
1
Order By: Relevance
“…Thus, it led to the inhibition of the activity of GSTs. Both induction and inhibition of GSTs in response to certain plant secondary metabolites by the enzyme inhibition assay have been reported [60, 61]. However, multiple studies have confirmed that the monoterpene compound showed a distinct enzyme inhibition [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it led to the inhibition of the activity of GSTs. Both induction and inhibition of GSTs in response to certain plant secondary metabolites by the enzyme inhibition assay have been reported [60, 61]. However, multiple studies have confirmed that the monoterpene compound showed a distinct enzyme inhibition [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…The values of MDA and EL were determined according to the method reported by Jiang and Zhang (2001). Moreover, the activities of antioxidant enzymes were assayed according to the methods reported by Mostofa et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…ROS like hydrogen peroxide (H 2 O 2 ), superoxide (O2⋅-), the hydroxyl radical (OH ⋅ ) and singlet oxygen ( 1 O2) are also produced as one of the earliest responses of plant cells to environmental stresses, and these ROS molecules can cause damage to a variety of biological processes (Halliwell, 2006; Gill and Tuteja, 2010; Das and Roychoudhury, 2014). In plants subjected to various abiotic stresses, such as salt, drought, chilling, heat and metal or metalloid stresses, ROS levels can rise significantly, leading to redox imbalance and oxidative stress (Hossain et al, 2010; Hasanuzzaman et al, 2011a,b; Hossain and Fujita, 2013; Mostofa and Fujita, 2013; Das and Roychoudhury, 2014; Mostofa et al, 2014a,b,c; Nahar et al, 2014). High ROS levels can result in extensive damage to proteins, DNA, and lipids, thereby affecting normal cellular functions, which can lead to permanent metabolic dysfunction and plant death (Anjum et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that priming can also modulate abiotic stress tolerance (Filippou et al, 2012; Hossain and Fujita, 2013; Mostofa and Fujita, 2013; Borges et al, 2014; Mostofa et al, 2014a,b,c; Nahar et al, 2014; Wang et al, 2014a). Despite the agronomic and ecological importance of priming, in-depth molecular mechanisms associated with priming in plants are still unknown (Conrath, 2011).…”
Section: Introductionmentioning
confidence: 99%